2015
DOI: 10.5483/bmbrep.2015.48.12.100
|View full text |Cite
|
Sign up to set email alerts
|

Phytosphingosine promotes megakaryocytic differentiation of myeloid leukemia cells

Abstract: We report that phytosphingosine, a sphingolipid found in many organisms and implicated in cellular signaling, promotes megakaryocytic differentiation of myeloid leukemia cells. Specifically, phytosphingosine induced several hallmark changes associated with megakaryopoiesis from K562 and HEL cells including cell cycle arrest, cell size increase and polyploidization. We also confirmed that cell type specific markers of megakaryocytes, CD41a and CD42b are induced by phytosphingosine. Phospholipids with highly sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…CD14 is the marker antigen of monocytes, and is mainly expressed in monocytes [26]. CD42b is the megakaryocyte differentiation antigen [10]. In the present study, the results showed that downregulation of SNHG5 significantly increased the expression of CD11b, CD14, and CD42b, indicating that K562 cells tended to differentiate into mature granulocytes, monocytes, and megakaryocyte.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…CD14 is the marker antigen of monocytes, and is mainly expressed in monocytes [26]. CD42b is the megakaryocyte differentiation antigen [10]. In the present study, the results showed that downregulation of SNHG5 significantly increased the expression of CD11b, CD14, and CD42b, indicating that K562 cells tended to differentiate into mature granulocytes, monocytes, and megakaryocyte.…”
Section: Discussionsupporting
confidence: 47%
“…The K562 cell line is a human myelogenous leukemia cell line from a highly undifferentiated progenitor of the megakaryocytic and erythrocytic lineages, with potential for erythroid and megakaryocyte differentiation, and it is currently the major cell model used for research of cellular differentation and screening of medical treatment for CML [8,9]. Differentiation-inducing therapy seems to be a promising strategy for CML [10,11], and the discover of a potential differentiation inducer or molecule has become an important focus of CML treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Staining for F-actin with phalloidin to delineate cellular boundaries and counterstaining with 4′-6-Diamidino-2-phenylindole (DAPI) were carried out as previously described (11).…”
Section: Methodsmentioning
confidence: 99%
“…Generation and purification of large quantities of TPO suitable for application in cell culture-based production is likely to be highly costly. Here, we describe an alternate strategy utilizing ( R )-TEMOSPho, a synthetic chemical previously shown to induce megakaryocytic differentiation of myeloid leukemia cells, as a supplement to TPO (11, 12). Specifically, we show that ( R )-TEMOSPho, which cannot by itself induce efficient MK differentiation of murine HSCs, can enhance TPO activity in megakaryocytic differentiation and plateletogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This gives researchers hope that they will eventually develop ways to force the AMKL cells to exit the proliferative cell cycle and undergo terminal differentiation (Wen et al ., ). A series of studies using agents that specifically promote the terminal differentiation of leukaemia cells into megakaryocytes are in development (Ojima et al ., ; Liu et al ., ; Han et al ., ). Of note, it has been demonstrated that autophagy is an important event for megakaryocytic differentiation of the human leukaemia cell line K562 (Colosetti et al ., ; Cao et al ., ), which has been extensively used as a model to study megakaryocyte differentiation.…”
Section: Introductionmentioning
confidence: 97%